ANALISIS KINERJA PELAYANAN PELABUHAN RAKYAT POUMAKO DALAM MENINGKATKAN KELANCARAN DISTRIBUSI BARANG KE WILAYAH PESISIR KABUPATEN MIMIKA - Nai Tiku; Rulan L Manduapessy (Jurnal Ekonomi dan Bisnis, 2024)
This research aims to determine the performance of Pomako people's port services in improving the smooth distribution of goods to the coastal areas of Mimika Regency. The method used in data analysis is the research method used in this research is the descriptive research method. The data used are primary data and secondary data, which were collected using documentation, interviews and surveys. To measure the effectiveness of the Poumako People's Port Service Performance Analysis in Improving the Smooth Distribution of Goods to the Coastal Areas of Mimika Regency, the Loading and Unloading Service Performance Indicator analysis tool is used as stipulated in the Regulation of the Director General of Sea Transportation Number: HK 103/2/2/DJPL-17 concerning Guidelines Calculation of Port Operational Service Performance, with development according to the objectives of this research. The results of this research show that Poumako People's Harbor has provided quite good performance in facilitating the distribution of goods to the coastal areas of Mimika Regency, this can be seen in the performance of goods loading and unloading services at Pomako People's Harbor. In the last 5 years (2017-2018).